Persuasive Technology for Managing the Routine of Families with Children and Adolescents with ADHD: A User-Centered Approach - Jandre, Caroline R. S.; Dal' Maria, Fernando C. S.; Nardy, Gabriel A. C.; Guimarães, Felipe T. G.; de Miranda, Débora M.; Nobre, Cristiane N. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that can significantly impact the social and academic functioning and daily routine of people diagnosed, as well as their families. Using Human-Computer Interaction (HCI) methods, this study has two main objectives: to identify the challenges in organizing the daily lives of families of children and adolescents with ADHD and to investigate strategies to engage those parents and/or responsible for managing their routine through technology. To achieve this, we conducted the study qualitatively, following the first three steps of the extended User-Centered Design (UCD) process. In the context stage, we carried out a documentary analysis of the literature on family routines related to ADHD and persuasive technologies. Then, in the elicitation phase, we used the collaborative co-creation approach in questionnaires and semi-structured interviews with those responsible for children and adolescents with ADHD. Finally, in the design stage, we explored the data collected to create a prototype tool that could help those responsible for managing the family's daily routine and promote their long-term involvement. As a result, we identify challenging everyday activities for children and teenagers with ADHD and tasks that their parents and/or responsible often forget. Furthermore, we analyzed how the perspectives of those responsible for managing family routines align with persuasive technological techniques in the literature, highlighting the features that proved to be important to them. The developed prototype offers features that help users obtain a more organized experience in managing daily activities. This work contributes to HCI by investigating and applying persuasive approaches to technologies aimed at well-being and mental health in the context of ADHD, seeking to reduce parental stress, improve communication, and promote more effective routine management for families affected by the disorder.